ANALISIS AKAD MUDHARABAH DALAM PENGELOLAAN DANA PENSIUN PADA BSI KC RANTAUPRAPAT - Naylatusalwa Makarim Tambunan; Muhammad Ikhsan Harahap (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to analyze the implementation of the mudharabah contract in pension fund management at BSI KC Rantauprapat. The research method used is qualitative with a case study approach. Data were obtained through interviews with the Branch Operation & Service Manager of BSI KC Rantauprapat and document analysis. The results showed that BSI KC Rantauprapat applies the mudharabah muthlaqah contract to its pension savings product, providing flexibility in fund investment. The associated risks are managed through investment diversification and strict supervision. This study highlights the need for more comprehensive regulations to support the development of Islamic pension funds. Recommended development strategies include increased education, product innovation, and strengthened risk management.